“REFUGEE CRISIS”: RE-THINKING THE INDONESIA’S PERSPECTIVE - Tisna, Ayu Bulan (Indonesian Law Journal, 2024)
Initiated by latest critical circumstances with Rohingyas, this study attempts to investigate the existing domestic policy and legal provision concerning refugees and asylum seekers in Indonesia. In this regard, qualitative and literature study has conducted, as well certain observation from empirical cases which also be adopted during this research. Whilst this research has found disadvantages over the refugee management in Indonesia and suggested the need for a better policy, rational decision-making model in this study offers a problem-solving focusing on objectivity and logic instead of subjectivity and intuition to achieve an intended and more appropriate arrangement to deal with the refugee crisis. Looking into the discursive refugee management of crises in Indonesia is important to understand their effects, at present and in the future. More than that, when it comes to policy, it is about capacity of the official policy on addressing issues to gain fruitful advantages for the country without violating human rights principles. Insight from maritime security is also being added to enrich the discussion on account that maritime is considered as crucial theatre regarding law enforcement at sea related to the main issue.